Chemical Effects of CO2 Concentration on Flame Structure and Soot Precursors in Rich Ethylene Oxidation - Zhang, Yindi; Lou, Chun; Li, Yong (Asian Journal of Chemistry, 2013)
Flame structure and soot precursors were investigated numerically with CO2 addition in fuel enrichment laminar premixed C2H4/O2/Ar flames (C/O ratio of F = 2.5) at low pressure (0.05 atm). An updated mechanism emphasizes the effect of presence of an O2/CO2 atmosphere instead of an O2/Ar one in premixed flame. The addition of CO2 in the fresh gas inlet causes a shift downstream of the flame front and thus flame inhibition. The partial replacement of Ar by CO2 leads to an increase of burnt gas quantities of H2O, CO and CO2 and leads to a decrease of the maximum mole fractions of some C2 to C10 hydrocarbon intermediates (C2H2, C3H3, C6H6, C6H6O, C8H8 and C10H8). The sensitivity analysis and reaction-path analysis show that C2H4 reaction path and products are altered due to the CO2 addition.